Martensitic stainless steel sheet for brake disc rotor, brake disc rotor, and method for manufacturing martensitic stainless steel sheet for brake disc rotor
Patent Information
- Application Number
- JP2023500764
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-18
- Filing Date
- 2022-02-08
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-02-08
Smart Images

Figure 0007640664000001 
Figure 0007640664000002 
Figure 0007640664000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a martensitic stainless steel sheet for brake disc rotors, which has excellent hardenability, formability, temper softening resistance and high-temperature strength, and a manufacturing method for a brake disc rotor and a martensitic stainless steel sheet for brake disc rotors.The present invention relates to a stainless steel sheet which has excellent productivity, reduces pad wear, has stable hardness, and is suitable for use in disc rotors and the like which require thin wall and light weight. [Background technology]
[0002] Disc brakes are widely used as one type of braking system. Disc brakes have a disk-shaped structure called a disc rotor that is connected to the tire. When the brake pads press against the disc rotor, friction is used to convert kinetic energy into thermal energy, slowing down the speed of the car or motorcycle. Disc rotors for disc brakes are hereinafter also referred to as "brake disc rotors."
[0003] In automobiles, flake graphite cast iron (hereafter referred to as cast iron) is used as the material for disc rotors due to its thermal conductivity and cost. Cast iron has poor corrosion resistance because it does not contain elements that improve corrosion resistance, and if left unattended, red rust will quickly form. Traditionally, this red rust was not very noticeable because the position of the disc rotor is lower than the line of sight and because of the shape of the wheel. However, in recent years, the wheel material has been changed to aluminum due to the demand for improved fuel efficiency, and the disc rotor has become more noticeable due to the thinner spokes of the wheel. As a result, rust on the disc rotor cannot be ignored, and there is a demand for improving the corrosion resistance of the disc rotor.
[0004] Furthermore, with the recent strengthening of environmental regulations, there is a strong demand for improved fuel efficiency in automobiles, which requires thinner and lighter disc rotors. However, cast iron has low strength, and since it is made by casting, there is a limit to how thin it can be. In addition, it is said that the maximum temperature reached when the brakes of an automobile are activated is close to 700°C. In addition, the temperature reached in driving conditions where braking is used frequently, such as on mountain roads, can be as high as 300°C. Cast iron has low high-temperature strength, and when thinned, it is not possible to ensure the strength required for a disc rotor at high temperatures, so there was an issue that it could not be made thinner and lighter. In addition, since cast iron is formed by casting, thinning the disc rotor may cause poor flow of the molten metal, making it impossible to form it.
[0005] Stainless steel is a material with excellent corrosion resistance, and martensitic stainless steel SUS410-based materials are widely used for motorcycles and other two-wheeled vehicles. This is because the disc rotors of motorcycles are exposed and easily visible, so corrosion resistance is important. However, stainless steel has the problem of being less thermally conductive than cast iron. In motorcycles, the brake system is exposed and has excellent cooling properties, so stainless steel is used without any problems in normal use. However, even in motorcycles, there is an issue that the disc rotors can become excessively heated under harsh braking conditions such as racing, resulting in increased wear of the brake pads.
[0006] On the other hand, in the case of automobiles, the brake system, including the tires, is housed inside the wheel housing, making it difficult to cool the disc rotor. As a result, stainless steel has a low thermal conductivity, which is one of the issues, and stainless steel has not been used for automobile disc rotors. However, in recent years, the adoption of "regenerative braking," which converts kinetic energy during driving into electrical energy and recovers it, has rapidly increased in EVs, FCVs, HVs, and other vehicles. This application reduces the frictional heat generated by the friction between the disc rotor and pads, expanding the possibility of using stainless steel, which has a lower thermal conductivity than cast iron.
[0007] Another issue that has prevented the use of stainless steel in automobile disc brakes is formability. Motorcycle disc rotors are ring-shaped disks that are stamped out of stainless steel sheets and then manufactured by induction hardening, so no major processing is required. On the other hand, current automobile disc rotors are hat-shaped, with the center of the disk squeezed in, and are manufactured by casting. Deep drawing is required to process and form such a shape using stainless steel sheets as the material. However, the stainless steel used in motorcycles is martensitic stainless steel, which is very hard and difficult to deep draw. As one way to solve this problem, hot stamping, which is press-formed at high temperatures, has become widespread in recent years. This has made it possible to precisely form hat shapes in stainless steel. In this context, in order to meet the recent demands for aesthetics, formability, and thin-walled, lightweight automobiles, it has become necessary to make disc rotors from stainless steel.
[0008] As mentioned above, in the case of automobiles, the brake system, including the tires, is housed inside the wheel housing, so the disc rotor is difficult to cool and has low thermal conductivity. Even in motorcycles, the disc rotor is overheated under harsh braking conditions such as during races. However, when martensitic stainless steel is held at high temperatures, C and N precipitates and dislocations are restored, resulting in tempering and softening. When tempering and softening occurs, there is a problem of excessive pad wear. In addition, abnormal wear of the disc rotor and brake pads can cause the braking effect to become unstable and the lifespan to be shortened. In other words, in order to apply martensitic stainless steel to automotive disc rotors, it is necessary to respond to the demand for reducing brake pad wear.
[0009] Patent documents 1 and 2 are related to stainless steel disc rotors. These documents describe steels with improved temper softening resistance by defining the prior austenite grain size and precipitated Nb. These documents relate to an invention that improves temper softening resistance at 600°C. Patent documents 3 and 4 describe steels with improved temper softening resistance by defining the prior austenite grain size and precipitated Nb and Cu. These documents relate to an invention that improves temper softening resistance at 650°C. Both inventions utilize precipitates that precipitate when exposed to high temperatures during braking when used as a part. If the time exposed to high temperatures is short, the time required for precipitation may not be reached. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Patent No. 4569360 [Patent Document 2] International Publication No. WO2008 / 044299 [Patent Document 3] International Publication No. WO2007 / 122754 [Patent Document 4] Patent No. 5200332 Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention relates to a stainless steel sheet for brake disc rotors, which has excellent hardenability, formability, temper softening resistance, and high-temperature strength. The parts that are the subject of the problem to be solved by the present invention are braking system parts, particularly disc rotors.
[0012] As mentioned above, the processing of stainless steel sheets into disc rotors is carried out by induction hardening since there is no major processing in motorcycles, and by hot stamping, which presses at high temperatures, for automobiles. Stainless steel sheets for hot stamping are manufactured by hot rolling and hot rolled sheet annealing. The high-temperature processing of hot stamping also serves as quenching processing. From the viewpoint of productivity, quenching heat treatment is preferably performed at a low temperature and for a short time. However, in conventional martensitic stainless steels, coarse Cr carbonitrides precipitate during hot rolled sheet annealing when manufacturing stainless steel sheets. In order to obtain sufficient hardness as a disc rotor, it is necessary to ensure solid solution C and N. Therefore, it was necessary to dissolve the coarse Cr carbonitrides precipitated in the stainless steel sheet by heating at a high temperature during quenching heat treatment. In other words, existing martensitic stainless steels require high-temperature heating during molding, and improving hardenability was necessary to improve productivity. Ensuring excellent hardenability, where Cr carbonitrides dissolve even in low-temperature and short-time heat treatment, is cited as a productivity issue for existing martensitic stainless steels.
[0013] Since automobile disk rotors are hat-shaped, the steel sheet must have formability, specifically, press formability at high temperatures during hot stamping to form the hat shape.
[0014] When a steel plate is used as a brake disc rotor, excellent temper softening resistance is required. The maximum temperature reached by a typical motorcycle is about 500°C, so martensitic stainless steels can be used, but the brake discs of four-wheeled vehicles and racing motorcycles have high temperatures, so temper softening occurs significantly, making them difficult to use. Patent documents 1 to 4 disclose temper softening resistance at 600°C and 650°C, but none of them disclose temper softening resistance at 700°C, which is required in the present invention.
[0015] Furthermore, when using steel plate for brake disc rotors, excellent high-temperature strength is required. The temperature that can be reached is about 100°C when driving in normal city areas, about 300°C when driving on mountain roads, and can reach a maximum of nearly 700°C, so strength in the medium to high temperature range is required to make the plate thinner.
[0016] The present invention provides a martensitic stainless steel sheet for brake disc rotors which has excellent hardenability and formability when the steel sheet is processed into brake disc rotors, and also has excellent temper softening resistance and high-temperature strength when used as a brake disc rotor; a brake disc rotor using the same; and a method for manufacturing a martensitic stainless steel sheet for brake disc rotors. [Means for solving the problem]
[0017] In order to solve the above problems, the present inventors conducted a detailed investigation focusing on the precipitates in stainless steel sheets. The steel sheets used for brake disc rotors, which are the subject of the present invention, are manufactured through hot rolling and hot rolled sheet annealing. Precipitates are precipitated in the steel sheets at the hot rolling stage and the hot rolled sheet annealing stage. The precipitates include Cr carbonitrides and other substances. Among these precipitates, the Cr carbonitride precipitates dissolve at low temperatures and in a short time when heated for forming by appropriately controlling their size and dispersion state, improving hardenability and improving productivity. In addition, precipitates other than Cr carbonitrides do not dissolve when heated for forming, and by being present finely in the product, the precipitates hinder the recovery of dislocations when used as parts, improving temper softening resistance. However, if the Cr carbonitride precipitates are coarse, high temperatures and long times are required for dissolution, resulting in reduced productivity. In addition, if the precipitates other than Cr carbonitrides are coarse, cracks are more likely to occur during hot stamp forming and use, and temper softening resistance is not improved, which may result in reduced high-temperature strength. Therefore, it was thought that by appropriately controlling the steel composition and hot rolling conditions, it would be possible to refine these precipitates in the steel sheet, thereby improving hardenability and thereby improving productivity, suppressing cracking during hot stamping, and suppressing a decrease in high-temperature strength while ensuring temper softening resistance when used as a part. As a result of various investigations conducted to achieve this objective, the following findings were obtained.
[0018] By appropriately controlling the steel composition, setting the heating temperature before hot rolling to 1000-1200°C, the hot rolling finishing temperature to 800°C or less, the cooling rate to 10°C / sec or more, and the coiling temperature to 550°C or less, the recovery of dislocations during hot rolling is suppressed, and the precipitates precipitated during hot rolling and hot rolled sheet annealing are refined. By refining the precipitates during hot rolling and hot rolled sheet annealing, first, the hardenability is improved by the refinement of Cr carbonitride precipitates, and the precipitates dissolve even at low temperatures and for a short time during quenching, and sufficient quenching hardness can be secured as a disc rotor. In addition, by refining precipitates other than Cr carbonitride, the tempering softening resistance during use as a part is improved, cracking during hot stamping is suppressed, and further, the decrease in high-temperature strength can be suppressed. Since the precipitates exist before use as a product sheet, i.e., as a part, high strength is exhibited even in a temperature range where tempering softening does not occur. The precipitates during hot rolling and annealing of hot-rolled sheets are mainly carbonitrides of Fe, Ti, Nb, V, Cu, Mo, W, Zr, Ta, Hf, etc., intermetallic compounds, and metallic Cu. As a result, we have succeeded in providing a stainless steel sheet that has excellent temper softening resistance, hardenability, formability, and high-temperature strength that can be used for disc rotors.
[0019] The gist of the present invention for solving the above problems is as follows. (1) In mass%, C: 0.001 to 0.500%, N: 0.001 to 0.500%, Si: 0.01 to 5.00%, Mn: 0.010-12.000%, P: 0.001 to 0.100%, S: 0.0001 to 1.0000%, Cr: 10.0-35.0%, Ni: 0.010~5.000%, Cu: 0.0010~3.0000%, Mo: 0.0010~3.0000%, Nb: 0.0010~1.0000%, V: 0.0010 to 1.0000% The balance is Fe and impurities. The average grain size of the precipitates in the matrix is 2 μm or less, and the precipitates are 0.01 to 20 particles / μm. 2 and has a quench hardness index A, represented by the following formula, of 200 to 800. A=2566[%C]+1282[%N]-12[%Si]+4[%Cu] -6[%Mo]-184[%Nb]-125[%V]+239 (2) Part of the Fe is replaced by, in mass%, Ti: 0.001 to 1.00%, B: 0.0001~0.0100%, Al: 0.001-4.0%, W: 0.001 to 3.0%, Sn: 0.001 to 1.00%, Mg: 0.0001 to 0.0100%, Sb: 0.001 to 0.50%, Zr: 0.001 to 1.000%, Ta: 0.001 to 1.00%, Hf: 0.001 to 1.000%, Co: 0.001 to 1.00%, Ca: 0.0001 to 0.0200%, REM: 0.001~0.50%, Ga: 0.0001 to 0.5000% The martensitic stainless steel sheet for a brake disc rotor according to (1), characterized in that it contains one or more of the following:
[0020] (3) A martensitic stainless steel sheet for brake disc rotors according to (1) or (2), characterized in that the fracture elongation at 1,050°C is 50% or more. (4) A martensitic stainless steel sheet for brake disc rotors according to any one of (1) to (3), characterized in that the martensitic stainless steel sheet for brake disc rotors has a hardness reduction of 150 Hv or less after further tempering at 700°C for 10 minutes, compared to the hardness when subjected to a hot stamping simulated heat treatment (hereinafter simply referred to as "simulated heat treatment") in which the sheet is heated to 1,050°C, held there for 5 seconds or more, and then water-cooled. (5) A martensitic stainless steel sheet for brake disc rotors according to any one of (1) to (4), characterized in that when the martensitic stainless steel sheet for brake disc rotors is subjected to a hot stamping simulated heat treatment (hereinafter simply referred to as "simulated heat treatment") in which the sheet is heated to 1,050°C, held there for 5 seconds or more, and then water-cooled, the 0.2% yield strength of the material at 700°C is 50 MPa or more.
[0021] (6) A brake disc rotor comprising the martensitic stainless steel sheet for brake disc rotors according to any one of (1) to (5).
[0022] (7) A method for producing a martensitic stainless steel sheet for a brake disc rotor according to any one of (1) to (5), characterized in that the finishing temperature during hot rolling is 800°C or less and the coiling temperature is 550°C or less.
[0023] The present invention improves the hardenability and formability of stainless steel plate, improves the temper softening resistance and high-temperature strength after simulated heat treatment of stainless steel plate, provides a material suitable for disc rotors of automobiles and motorcycles, and has a significant effect on improving appearance and safe braking in a variety of environments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The grounds for specifying the content of each element in steel are described below.
[0025] Here, the martensitic stainless steel sheet means a stainless steel sheet in which the martensite phase accounts for 80% or more of its area when the steel sheet is subjected to a quenching treatment. In the case of a hot-rolled sheet (stainless steel sheet before hot-rolling and annealing), the martensite phase accounts for the majority, while in the case of a hot-rolled and annealed sheet (stainless steel sheet of the present invention), the ferrite phase accounts for the majority, and after quenching treatment by hot stamping (brake disc rotor of the present invention), the structure is a martensite phase or a martensite phase + ferrite phase. In some cases, a small amount of austenite phase remains.
[0026] A preferred composition (mass %) of the stainless steel sheet of the present invention will be described below. C is an element that dissolves in the matrix and has a large effect on hardness. Depending on the heat treatment, it can produce carbides, which can deteriorate formability and corrosion resistance, and reduce high-temperature strength, so the content is set at (A). Also, excessive reduction in the content leads to increased refining costs, so the content of (B) is preferable. Even more preferable is the content of (C). (A)=0.001~0.500%, (B)=0.010~0.300%, (C) = 0.030~0.070%.
[0027] Like C, N is an element that dissolves in the matrix and has a large effect on hardness. Depending on the heat treatment, it can produce nitrides that deteriorate formability and corrosion resistance, and reduce high-temperature strength, so the content is set at (A). Also, excessive reduction leads to increased refining costs, so the content is preferably (B). Even more preferably, the content is set at (C). (A)=0.001~0.500%, (B)=0.010~0.100%, (C)=0.020~0.050%.
[0028] Silicon is a useful element as a deoxidizer, and also improves oxidation resistance and resistance to high-temperature salt damage. However, excessive addition reduces room temperature ductility, so the content is set at (A). However, when considering pickling properties and toughness, the content of (B) is more preferable. Furthermore, when considering manufacturability, the content of (C) is more preferable. (A)=0.01~5.00%, (B)=0.10 to 1.00%, (C)=0.20~0.40%.
[0029] Mn is an element added as a deoxidizer, and contributes to increasing high-temperature strength in the medium temperature range. However, excessive addition causes Mn-based oxides to form on the surface at high temperatures, which can lead to poor scale adhesion and abnormal oxidation. In particular, when added in combination with Mo or W, there is a tendency for abnormal oxidation to occur more easily relative to the amount of Mn, so the content is set at (A). Furthermore, when considering the pickling properties and room temperature ductility in steel sheet manufacturing, the content of (B) is preferable. The content of (C) is even more preferable. (A)=0.010~12.000%, (B)=0.400~2.000%, (C) = 1.000~1.500%.
[0030] P is an impurity that is mainly mixed in from raw materials during steelmaking and refining, and if the content is high, toughness and weldability decrease. For this reason, it is desirable to reduce it as much as possible, but to reduce it to less than 0.001%, the cost will increase due to the use of low-P raw materials, so in the present invention, it is set to 0.001% or more. On the other hand, if it contains more than 0.100%, it will significantly harden and the corrosion resistance, toughness and pickling properties will deteriorate, so the upper limit is set to 0.100%. In consideration of raw material costs, it is desirable to set it to 0.008 to 0.080%, and more desirably 0.010 to 0.050%.
[0031] S is an element that deteriorates corrosion resistance and oxidation resistance, but it not only improves workability by combining with Ti and C, but also forms sulfides by combining with Cr, Mn, etc., and exhibits lubricity. Since this effect is manifested from 0.0001%, the lower limit is set to 0.0001%. On the other hand, excessive addition of S combines with Ti and C to reduce the amount of solid-solubilized Ti and cause coarsening of precipitates, which reduces high-temperature strength, so the upper limit is set to 1.0000%. Furthermore, considering refining costs and high-temperature oxidation properties, the content is preferably 0.0005 to 0.0500%. More preferably, the content is set to 0.0010 to 0.0100%.
[0032] In the present invention, Cr is an essential element for ensuring oxidation resistance and corrosion resistance. When the content is small, oxidation resistance cannot be ensured, and excessive addition leads to a decrease in workability and a deterioration in toughness, so the content is set to (A). Furthermore, in consideration of manufacturability and scale spalling properties, the content is preferably (B). More preferably, the content is set to (C). (A)=10.0~35.0%, (B)=10.5-15.0%, (C)=11.0~13.0%.
[0033] Ni is an element that improves oxidation resistance, toughness, and high-temperature strength, and is added as necessary. However, excessive addition increases costs, so the content is set to (A). Considering manufacturability, the content of (B) is preferable, and the content of (C) is even more preferable. (A)=0.010~5.000%, (B)=0.030~0.600%, (C)=0.050~0.080%.
[0034] Cu is an element effective in improving corrosion resistance. Temper softening resistance and high-temperature strength are improved through precipitation strengthening due to ε-Cu precipitation, but excessive addition reduces hot workability, so the content is set at (A). Furthermore, taking into consideration thermal fatigue properties, manufacturability, and weldability, the content is set at (B). Even more preferable is the content of (C). (A)=0.0010~3.0000%, (B)=0.0100~2.0000%, (C) = 0.2000~1.6000%.
[0035] Mo is an element that is effective in solid solution strengthening at high temperatures, and is added to improve temper softening resistance, corrosion resistance, and high-temperature salt damage resistance. Excessive addition significantly deteriorates room temperature ductility and oxidation resistance, so the content is set at (A). Furthermore, taking into consideration thermal fatigue properties and manufacturability, the content is preferably (B). Even more preferably, the content is set at (C). (A)=0.0010~3.0000%, (B)=0.0100~1.0000%, (C) = 0.0300~0.5000%.
[0036] Nb is an element that is effective in improving temper softening resistance and high-temperature strength through solid solution strengthening and precipitation strengthening of fine precipitates. It also fixes C and N as carbonitrides, and contributes to the development of recrystallization texture that affects the corrosion resistance and r-value of the finished sheet (hot-rolled annealed sheet). Excessive addition significantly hardens the steel and also deteriorates manufacturability, so the content is set at (A). Furthermore, taking into consideration raw material costs and toughness, the content is preferably (B). Even more preferably, the content is set at (C). (A)=0.0010~1.0000%, (B)=0.0100~0.7000%, (C) = 0.1000~0.5000%.
[0037] V is an element that improves corrosion resistance, but if added in excess, it causes precipitates to become coarse, reducing temper softening resistance and high-temperature strength, as well as deteriorating oxidation resistance, so the content is set to (A). Furthermore, taking into consideration production costs and manufacturability, the content is preferably (B), and even more preferably (C). (A)=0.0010~1.0000%, (B)=0.0030~0.5000%, (C) = 0.1000~0.4000%.
[0038] The steel plate of the present invention is further characterized in that the hardness index A, which is expressed by the following formula based on the content of each component, is 200 to 800. In the formula, [% element symbol] means the content (mass%) of the corresponding element. When the hardness index A is 200 or more, a hardness sufficient for use as a brake disc rotor can be obtained. When the hardness index A exceeds 800, the hardness becomes excessively large and the toughness becomes insufficient during use. A=2566[%C]+1282[%N]-12[%Si]+4[%Cu] -6[%Mo]-184[%Nb]-125[%V]+239
[0039] In the present invention, the balance is Fe and impurities. Furthermore, if necessary, the following components may be contained in place of a portion of the Fe.
[0040] Ti is an element that combines with C, N, and S to improve corrosion resistance, intergranular corrosion resistance, room temperature ductility, and deep drawability. In addition, when added in combination with Nb and Mo, adding an appropriate amount increases the amount of solid solution of Nb and Mo during hot rolling and annealing, improves high-temperature strength, and improves tempering softening resistance and thermal fatigue properties. The effect is manifested from 0.001% or more, so the lower limit is set to 0.001%. On the other hand, adding more than 1.00% increases the amount of solid solution Ti, reducing room temperature ductility, and forms coarse Ti-based precipitates that become the starting point of cracks during hole expansion processing, deteriorating press formability. In addition, oxidation resistance is also deteriorated, so the amount of Ti added is set to 1.00% or less. Furthermore, considering the occurrence of surface defects and toughness, 0.001 to 0.20% is preferable.
[0041] B is an element that improves secondary workability during press forming of products, high-temperature strength, and thermal fatigue properties. B brings about fine precipitation of Laves phases and the like, and realizes the long-term stability of these precipitation strengthening, thereby contributing to suppressing strength reduction and improving thermal fatigue life. This effect is realized at 0.0001% or more. On the other hand, excessive addition brings about hardening, deteriorates intergranular corrosion resistance and oxidation resistance, and also causes weld cracks, so the content is set to 0.0100% or less. Furthermore, considering corrosion resistance and manufacturing costs, 0.0001 to 0.0050% is preferable. More preferably, 0.0001 to 0.0020% is preferable.
[0042] Al is added as a deoxidizing element and also improves oxidation resistance. It is also useful as a solid solution strengthening element for improving high temperature strength and temper softening resistance. This effect is stably manifested from 0.001%. On the other hand, excessive addition hardens the steel and significantly reduces uniform elongation as well as toughness, so the upper limit is set at 4.0%. Furthermore, in consideration of the occurrence of surface defects, weldability, and manufacturability, 0.003 to 2.0% is preferable.
[0043] W, like Mo, is an effective element for solid solution strengthening at high temperatures and is also an effective element for the Laves phase (Fe 2 In particular, when added in combination with Nb or Mo, Fe 2 The Laves phase of (Nb, Mo, W) precipitates, but adding W suppresses the coarsening of this Laves phase, improving the precipitation strengthening ability and tempering softening resistance. This effect occurs when adding 0.001% or more. On the other hand, adding more than 3.0% increases the cost and reduces room temperature ductility, so the upper limit is set at 3.0%. Furthermore, considering manufacturability, low temperature toughness, and oxidation resistance, the amount of W added is preferably 0.001 to 1.5%.
[0044] Sn is an element that improves corrosion resistance and improves high-temperature strength in the medium temperature range, so it is added as necessary. These effects are manifested at 0.001% or more. On the other hand, adding more than 1.00% significantly reduces manufacturability and toughness, so the content is set to 1.00% or less. Furthermore, taking into consideration oxidation resistance and manufacturing costs, 0.01 to 0.10% is preferable.
[0045] Mg is sometimes added as a deoxidizing element, and also refines the structure of the slab, contributing to improved formability. In addition, Mg oxides become precipitation sites for carbonitrides such as Ti(C,N) and Nb(C,N), and have the effect of finely dispersing and precipitating these. This effect is manifested at 0.0001% or more, and contributes to improving toughness. However, excessive addition leads to deterioration of weldability, corrosion resistance, and surface quality, so the upper limit is set at 0.0100%. Considering refining costs, 0.0003 to 0.0010% is desirable.
[0046] Sb contributes to improving corrosion resistance and high-temperature strength, so 0.001% or more is added as necessary. The upper limit is set to 0.50% because the addition of more than 0.50% may cause slab cracking and excessive reduction in ductility during steel plate production. Furthermore, considering refining costs and manufacturability, 0.01 to 0.30% is preferable.
[0047] Zr, like Ti and Nb, is a carbonitride forming element and improves corrosion resistance and deep drawability, and is added as necessary. These effects are manifested at 0.001% or more. On the other hand, the addition of more than 1.000% significantly deteriorates manufacturability, so the content is set to 1.000% or less. Furthermore, taking into consideration the cost and surface quality, 0.001 to 0.200% is preferable.
[0048] Ta and Hf combine with C and N to improve toughness, so they are added at 0.001% or more as necessary. However, the addition of more than 1.00% increases costs and significantly deteriorates manufacturability, so the upper limit is set at 1.00%. Furthermore, considering refining costs and manufacturability, 0.01 to 0.08% is preferable.
[0049] Co contributes to improving high-temperature strength, so 0.001% or more is added as necessary. Addition of more than 1.00% leads to deterioration of toughness, so the upper limit is set to 1.00%. Furthermore, taking into consideration refining costs and manufacturability, 0.01 to 0.10% is preferable, and 0.01 to 0.03% is even more preferable.
[0050] Ca is sometimes added for desulfurization, and this effect is manifested at 0.0001% or more. However, the addition of more than 0.0200% generates coarse CaS, which deteriorates toughness and corrosion resistance, so the upper limit is set at 0.0200%. Furthermore, in consideration of refining costs and manufacturability, a Ca content of 0.0003 to 0.0020% is preferable.
[0051] REM may be added as necessary from the viewpoint of improving toughness and oxidation resistance by refining various precipitates, and this effect is manifested at 0.001% or more. However, the addition of more than 0.50% significantly deteriorates castability and reduces ductility, so the upper limit is set at 0.50%. Furthermore, considering refining costs and manufacturability, 0.001 to 0.05% is preferable. According to the general definition, REM (rare earth elements) refers to two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). They may be added alone or as a mixture.
[0052] Ga may be added in an amount of 0.5000% or less to improve corrosion resistance and suppress hydrogen embrittlement. From the viewpoint of sulfide and hydride formation, the lower limit is preferably set to 0.0001%. Furthermore, from the viewpoints of manufacturability and cost, as well as ductility and toughness, the amount is preferably 0.0020% or less.
[0053] Other components are not particularly specified in the present invention, but in the present invention, Bi, etc. may be added in an amount of 0.001 to 0.1% as necessary. It is preferable to reduce the amount of general harmful elements and impurity elements such as As and Pb as much as possible.
[0054] In the present invention, it is important that the precipitates in the product sheet (hot-rolled annealed sheet) are finely present from the viewpoints of productivity (hardenability) during forming, formability, and tempering softening resistance and high-temperature strength during use. To achieve this, the components of each element are appropriately controlled, and dislocations are made difficult to recover during hot rolling, and dislocations are made into nucleation sites. In order to suppress the recovery of dislocations during hot rolling, the hot rolling finishing temperature is 800°C or less, the cooling rate is 10°C / sec or more, and the coiling temperature is 550°C or less. It has also been found that precipitates must be present in the product sheet (hot-rolled annealed sheet) with a specific size and density. The precipitates are classified into Cr carbonitride precipitates and other precipitates. The other precipitates are mainly carbonitrides of Fe, Ti, Nb, V, Cu, Mo, W, Zr, Ta, Hf, etc., intermetallic compounds, and metallic Cu.
[0055] Specifically, in stainless steel sheets for brake disc rotors (after hot-rolled annealing), the average grain size of precipitates present in the parent phase is 2 μm or less, and the precipitates are 0.01 to 20 particles / μm. 2 It is specified that the precipitates exist at a density of 1000 to 2000 K. Note that some precipitates dissolve at the quenching heat treatment temperature, while others do not. Cr carbonitrides dissolve, but other precipitates are almost insoluble.
[0056] Processing into disc rotors is performed by hot stamping and induction hardening, and the heating time for hardening heat treatment is generally very short for the sake of productivity. To obtain sufficient hardness for a disc rotor, the Cr carbonitrides that precipitate during hot rolling or annealing of the hot-rolled sheet must dissolve and solute C and N even with short heating times. The fine presence of Cr carbonitrides allows them to dissolve easily, helping to ensure solute C and N and improving hardenability. The average grain size of the precipitates in the parent phase is 2μm or less, and the precipitates are 0.01-20 particles / μm. 2 The Cr carbonitrides are finely dispersed at a density of 1 μm, so that they dissolve even in a short heating period during quenching. If the average grain size exceeds 2 μm, the Cr carbonitrides cannot be completely dissolved in a short heating period during quenching, and sufficient solute C and N cannot be secured, resulting in insufficient quenching hardness. Prolonging the heating time impedes productivity.
[0057] Precipitates other than Cr carbonitrides are hardly dissolved by heating for quenching heat treatment, and their fine presence in the product after forming and quenching prevents the movement of dislocations, which contributes to improving temper softening resistance and suppressing the decrease in high-temperature strength. In addition, finer precipitates are less likely to become the starting point of cracks during processing, improving formability. That is, the average grain size of the precipitates in the matrix is 2 μm or less, and the precipitates are 0.01 to 20 pieces / μm. 2 When present in a fine precipitate at a density of 0.1 to 100 μm, the precipitates effectively impede the movement of dislocations, thereby contributing to improvement of temper softening resistance and high-temperature strength.
[0058] If the average grain size of the precipitates exceeds 2 μm, they do not provide resistance to the movement of dislocations, and contribute little to improving temper softening resistance and high-temperature strength. They also tend to become the starting point of cracks during hot stamping and use, impairing formability. If the density of the precipitates is 0.01 particles / μm 2 If the density of precipitates is less than 20 / μm, the pinning interval of dislocations becomes wider, making it difficult for the precipitates to resist the movement of dislocations. 2 If the thickness exceeds 100 μm, the strength is excessively increased and cracks are easily generated. From the above, the precipitates in the matrix after hot-rolled sheet annealing have an average grain size of 2 μm or less and a grain size of 0.01 to 20 precipitates / μm. 2 It is specified that the material exists at a density of
[0059] The average grain size of the precipitates is preferably 5 nm or more and 1.5 μm or less, and more preferably 5 nm or more and 1.0 μm or less. The density of the precipitates is 0.1 particles / μm. 2 More than 20 pieces / μm 2 It is preferable that the density is less than 1 particle / μm. 2 More than 20 pieces / μm 2 The following is the result. This resulted in the successful provision of a stainless steel sheet suitable for use in disc rotors.
[0060] The precipitates can be identified by observation using a transmission electron microscope (e.g., a 200 kV field emission transmission electron microscope JEM2100F manufactured by JEOL Ltd.) and analysis using an attached EDS device (e.g., a 200 kV field emission transmission electron microscope JEM2100F manufactured by JEOL Ltd.). Samples were collected by ion milling so that the steel sheet was observed at a depth of t / 4 (t is the thickness of the steel sheet) in the thickness direction, and 10 arbitrary points were observed and analyzed at 50,000 times magnification. At this magnification, it is possible to observe the state of the precipitates almost uniformly. In addition, the composition of Fe, Cr, Si, Mn, Ti, Nb, V, Cu, Mo, W, Zr, Ta, and Hf was quantified in mass% at the same observation points using an EDS device, and precipitates were detected when values equal to or greater than the amounts of the steel sheet components added were detected. To calculate the particle size and density of the precipitates, the sample was observed in the same way, and after observing these areas, only the precipitates were colored and the images were processed. The particle size of each particle was then calculated as the equivalent circle diameter using NIH's image analysis software "ImageJ," and the average particle size and average density of the five fields of view were then calculated.
[0061] The martensitic stainless steel sheet for brake disc rotors of the present invention is characterized in that it has a breaking elongation of 50% or more at 1,050° C. This allows the steel sheet to achieve excellent formability.
[0062] The martensitic stainless steel sheet for brake disc rotors of the present invention is characterized in that, compared to the hardness when subjected to a hot stamp simulated heat treatment (simulated heat treatment) in which the sheet is heated to 1,050°C, held there for 5 seconds or more, and then water-cooled, the hardness drop after further tempering at 700°C for 10 minutes after the simulated heat treatment is 150 Hv or less. This makes it possible to achieve excellent temper softening resistance as a brake disc rotor.
[0063] The martensitic stainless steel sheet for brake disc rotors of the present invention is characterized in that, when subjected to the quasi-heat treatment, the material has a 0.2% yield strength of 50 MPa or more at 700° C. This makes it possible to realize excellent high-temperature strength for brake disc rotors.
[0064] The brake disc rotor of the present invention is made using the martensitic stainless steel sheet for brake disc rotors of the present invention. Specifically, the martensitic stainless steel sheet for brake disc rotors of the present invention is formed into the shape of a brake disc rotor by hot stamp forming, and quenched by heat treatment during hot stamp forming. The martensitic stainless steel sheet has excellent temper softening resistance and excellent high-temperature strength.
[0065] Next, the manufacturing method will be described. The method for manufacturing stainless steel sheet for brake disc rotors of the present invention comprises the steps of steelmaking, hot rolling, annealing, and pickling. In steelmaking, a method is suitable in which steel containing the above-mentioned essential components and components added as necessary is melted in a converter and then subjected to secondary refining. The melted steel is made into slabs by a known casting method (continuous casting).
[0066] The slab is heated to a predetermined temperature and hot rolled to a predetermined thickness by continuous rolling. The hot rolling is performed by rolling in a hot rolling mill consisting of multiple stands and then coiled. By finely precipitating the carbonitrides precipitated by annealing after hot rolling, the carbonitrides can be dissolved in the parent phase even with short heating during hot stamping. In order to finely precipitate the carbonitrides, it is sufficient to make the dislocations difficult to recover during hot rolling and use the dislocations as nucleation sites. In order to suppress the recovery of dislocations during hot rolling, the hot rolling finishing temperature is 800°C or less and the coiling temperature is 550°C or less. From the viewpoint of productivity, the finishing temperature is preferably 750°C or less and the coiling temperature is 500°C or less. More preferably, the finishing temperature is 700°C or less and the coiling temperature is 450°C or less, and the finishing temperature is more preferably less than 700°C. The cooling rate between finishing and coiling is preferably 10°C / sec or more and less than 25°C / sec.
[0067] The coiled hot-rolled coil is annealed at a specified temperature in an annealing furnace and then pickled. The annealing temperature is 820°C to 900°C for 3 hours to 5 hours. The existing pickling method can be applied.
[0068] The martensitic stainless steel sheet for brake disc rotors manufactured in this manner can be used with a sheet thickness of 2.0 mm or more and 15.0 mm or less. Taking into consideration the rigidity and weight of the brake disc rotor, the sheet thickness is preferably 3.0 mm or more and 13.0 mm or less, and more preferably 4.1 mm or more and 9.0 mm or less. EXAMPLES
[0069] Steels having the chemical compositions shown in Tables 1 and 2 were melted and cast into ingots, which were then hot-rolled to a thickness of 6 mm. The hot-rolling finishing temperature and hot-rolling coiling temperature shown in Tables 3 and 4 were used, and the cooling rate between finishing and coiling was 12°C / sec. The hot-rolled sheets obtained were held at 850°C for 4 hours and cooled to room temperature to obtain hot-rolled annealed sheets. Nos. A1 to A34 in Tables 1 and 2 are steels according to the present invention, and Nos. B1 to B13 in Table 2 are comparative steels. Values outside the scope of the present invention are underlined.
[0070] In order to evaluate the press formability at high temperatures of the hot-rolled annealed sheet before hot stamping, a high-temperature tensile test piece was taken from the hot-rolled annealed sheet so that the rolling direction was the tensile direction, and a tensile test was performed at 1050°C to measure the breaking elongation (based on JIS G 0567, with the values rounded off to the nearest whole number). Here, if the breaking elongation at 1050°C is 50% or more, it can be formed into a hat shape, so those having a breaking elongation at 1050°C of 50% or more were judged to pass (marked with "A" in "press formability" in Tables 3 and 4). Those that did not pass were marked with "X" in Tables 3 and 4. The same applies to the evaluation of the hardenability, tempering softening resistance after hot stamping, and high-temperature strength of the steel sheets described below.
[0071] The hot-rolled annealed sheets were subjected to a simulated hot stamping heat treatment (hereinafter simply referred to as "simulated heat treatment") in which the sheets were heated to 1050°C, held there for 5 seconds or more, and then water-cooled. After the simulated heat treatment, the steel sheets were pickled. The hardenability, tempering softening resistance after hot stamping, and high-temperature strength of the steel sheets were evaluated after the simulated heat treatment.
[0072] In order to evaluate the hardenability, test pieces were prepared by heat treatment of 900℃×1sec and then water cooling, and 1100℃×1sec and then water cooling (hereinafter referred to as "900℃ quenched heat treated material" and "1100℃ quenched heat treated material"). Vickers hardness was measured (based on JIS Z 2244, t / 2 part, load 5kg, average value of n=5 is taken as hardness. Values are rounded off to the nearest whole number). Here, if the difference in hardness between the 900℃ quenched heat treated material and the 1100℃ quenched heat treated material is 50 Hv or less, it can be applied to general disc rotors, so the material with the difference in hardness between the 900℃ quenched heat treated material and the 1100℃ quenched heat treated material of 50 Hv or less was deemed to pass (marked "A" in "hardenability" in Tables 3 and 4).
[0073] To evaluate temper softening resistance, test pieces were prepared by tempering the pseudo-heat-treated material at 700℃ for 10 minutes (hereinafter referred to as "tempered softening treated material") and Vickers hardness was measured (based on JIS Z 2244, t / 2 part, load 5kg, average value of n=5 is taken as hardness. Values are rounded off to the nearest whole number). Here, if the difference in hardness between the pseudo-heat-treated material and the tempered softening treated material is 150 Hv or less, it can be applied to general disc rotors, so the material was deemed to pass if the difference in hardness between the pseudo-heat-treated material and the tempered softening treated material was 150 Hv or less (marked "A" in "Temper softening resistance" in Tables 3 and 4).
[0074] To evaluate the strength during use, high-temperature tensile test pieces were taken from the pseudo-heat-treated material so that the rolling direction was the tensile direction, and a tensile test was carried out at 700°C to measure the 0.2% yield strength (based on JIS G 0567, with values rounded off to the nearest whole number). If the 0.2% yield strength at 700°C is 50 MPa or more, it can be used in general disc rotors and can be made thinner, so those with a 0.2% yield strength of 50 MPa or more at 700°C were deemed to have passed (marked with an "A" in "High-temperature strength" in Tables 3 and 4).
[0075] [Table 1]
[0076] [Table 2]
[0077] [Table 3]
[0078] [Table 4]
[0079] As is clear from Tables 3 and 4, the hardenability, press formability, temper softening resistance after simulated heat treatment, and 0.2% yield strength at 700°C of the steel plate of the present invention examples are superior to those of the comparative examples. If any one of the above differences in hardness after quenching at 900°C and 1100°C, the difference in hardness before and after tempering, the fracture elongation at 1050°C, and the 0.2% yield strength at 700°C was not met, it was determined that the steel was unsuitable for use as a disc rotor. This shows that the steel specified in the present invention is excellent in hardenability, temper softening resistance, formability, and high-temperature strength.
[0080] In Comparative Examples B1 and B2, the C and N concentrations were outside the upper limits, and large amounts of coarse carbonitrides precipitated, so that the Cr carbides were not sufficiently dissolved by the pseudo heat treatment, and the tempering softening resistance was poor. In addition, the coarse carbonitrides did not contribute to precipitation strengthening and became the starting points of cracks, so the 0.2% proof stress and press formability at 700°C were poor. In Comparative Example B3, the Si concentration was outside the upper limit. Si increases the activity of C, causing the precipitation of coarse carbides, resulting in insufficient temper softening resistance, 0.2% proof stress at 700°C, and press formability. In Comparative Example B4, the Mn concentration was below the lower limit, and the 0.2% proof stress at 700°C was insufficient. In Comparative Example B5, the P concentration was outside the upper limit, and a large amount of coarse phosphides precipitated, resulting in insufficient 0.2% yield strength at 700° C. In addition, press formability was insufficient due to hardening. In Comparative Example B6, the S concentration was outside the upper limit, which caused the Ti-based precipitates to become coarse, and the 0.2% proof stress at 700°C was insufficient. In Comparative Example B7, the Cr concentration was outside the upper limit, and a large amount of coarse Cr carbonitrides precipitated, so that the hardenability, temper softening resistance, and 0.2% yield strength at 700° C. were insufficient. In addition, the press formability was poor due to hardening. In Comparative Example B8, the Cu concentration was below the lower limit, and therefore Cu precipitation did not occur sufficiently, leading to insufficient precipitation strengthening and resulting in insufficient temper softening resistance and 0.2% proof stress at 700°C. In Comparative Examples B9, 10 and 11, the Mo, Nb and V concentrations were below the lower limits, respectively, and precipitates containing each element were not sufficiently precipitated, resulting in insufficient precipitation strengthening and insufficient temper softening resistance and 0.2% yield strength at 700°C.
[0081] In Comparative Example B12, the hot rolling finish temperature and hot rolling coiling temperature were outside the upper limits, and the Cr carbonitrides and precipitates were excessively coarsened, resulting in poor temper softening resistance, 0.2% proof stress at 700°C, and press formability. In Comparative Example B13, the Ni concentration was below the lower limit, and the 0.2% proof stress at 700°C was insufficient.
Claims
1. In mass%, C: 0.001 to 0.500%, N: 0.001-0.500%, Si: 0.01-5.00%, Mn: 0.010-12.000%, P: 0.001-0.100%, S: 0.0001-1.0000%, Cr: 10.0-35.0%, Ni: 0.010-5.000%, Cu: 0.0010-3.0000%, Mo: 0.0010-3.0000%, Nb: 0.0010 to 1.0000%, V: 0.0010 to 1.0000%; The balance is Fe and impurities, the average grain size of the precipitates present in the matrix is 2 μm or less, and the precipitates are 0.01 to 20 pieces / μm 2 and has a hardness index A of 200 to 800, which is represented by the following formula: The elongation at break at 1050°C is 50% or more, A martensitic stainless steel sheet for brake disc rotors, characterized in that when subjected to a hot stamping simulated heat treatment (hereinafter simply referred to as "simulated heat treatment") in which the sheet is heated to 1,050°C, held there for 5 seconds or more, and then water-cooled, the material has a 0.2% yield strength of 50 MPa or more at 700°C. A=2566[%C]+1282[%N]-12[%Si]+4[%Cu] -6[%Mo]-184[%Nb]-125[%V]+239
2. In place of a part of the Fe, Ti: 0.001 to 1.00%, B: 0.0001 to 0.0100%, Al: 0.001-4.0%, W: 0.001-3.0%, Sn: 0.001 to 1.00%, Mg: 0.0001-0.0100%, Sb: 0.001 to 0.50%, Zr: 0.001 to 1.000%, Ta: 0.001 to 1.00%, Hf: 0.001-1.000%, Co: 0.001 to 1.00%, Ca: 0.0001-0.0200%, REM: 0.001-0.50%, 2. The martensitic stainless steel sheet for brake disc rotors according to claim 1, further comprising at least one of the following elements: Ga: 0.0001 to 0.5000%.
3. 3. A martensitic stainless steel sheet for brake disc rotors according to claim 1 or 2, characterized in that the reduction in hardness after the pseudo heat treatment and further tempering at 700°C for 10 minutes is 150 Hv or less compared to the hardness after the pseudo heat treatment.
4. A brake disc rotor comprising the martensitic stainless steel sheet for brake disc rotors according to any one of claims 1 to 3.
5. The method for producing a martensitic stainless steel sheet for brake disc rotors according to any one of claims 1 to 3, characterized in that the finishing temperature during hot rolling is 800°C or less, and the coiling temperature is 550°C or less.
Citation Information
Patent Citations
Nonnaqueous electrolyte battery
JP1977000332A
Hot stamp molded body excellent in strength and hydrogen embrittlement resistance and its manufacturing method
JP2014118613A
Martensite stainless cold rolled steel sheet for automobile disc brake rotor, excellent in hardening property and corrosion resistance, steel band, and manufacturing method therefor
JP2019065373A
Stainless steel sheet and braking component
JP2019178419A
Method for producing martensitic stainless steel parts from sheet
JP2019518609A